G Protein-Coupled Estrogen Receptor 1 Knockout Deteriorates MK-801-Induced Learning and Memory Impairment in Mice - Zhang, Chun; Liu, Qiang; Yu, Chun-Yang; Wang, Feng; Shao, Yu; Sun, Kui-Sheng; Sun, Tao; Liu, Juan (Frontiers in Behavioral Neuroscience, 2020)
The role of estrogen receptors in neuroprotection and cognition has been well studied in human subjects over the past 20 years. Recently, studies have shifted their focus to the use of selective estrogen receptor modulators in the treatment of mental illnesses in the central nervous system. Thus, we conducted this study to test the behavioral changes shown by G protein-coupled estrogen receptor 1 knock-out(GPER1 KO） and wild-type (WT) mice with MK-801-induced schizophrenia (SZ). GPER1 KO and WT mice received intraperitoneal injections of MK-801 for 14 continuous days. Behavioral, learning and memory and social interaction changes were evaluated by using the IntelliCage system, open-field, three-chamber social interaction, and novel object recognition tests. The protein expression levels of the NR2B/CaMKII/CREB signaling pathway were tested via Western blot analysis. The KO SZ group were more likely to show impaired long-term learning and memory function than the WT SZ group. Moreover, learning and memory function were also impaired in the KO Con group. MK-801 administration to the GPER1-KO and WT groups resulted in memory deficiencies and declining learning capabilities. GPER1 deficiency down-regulated the expression levels of proteins related to the NR2B/CaMKII/CREB signaling pathway.